Manajemen Operasional Masjid Namira Lamongan sebagai Aset Wakaf - Ilmiyah, Izzatul; Zaman, Badaruz (Journal of Islamic Finance and Syariah Banking, 2024)
The research entitled "Operational Management of the Namira Lamongan Mosque as a Waqf Asset" is the result of qualitative research that aims to answer the question of how Naẓir's strategy in operational management is implemented at the Namira Mosque as a waqf asset in the form of a mosque to make the mosque prosperous. and what impact the implementation of operational management will have on the congregation and community. The research results show that the naẓir strategy in operational management implemented by the taker of the Namira Mosque is modern mosque operational management which is implemented through three areas, namely Idarah, Imarah, and Ri'yah. Idarah is the function of mosque management, which is related to all mosque operational activities. Imarah is the function of prospering the mosque as the function of the mosque is the function of worship, and Ri'yah is the function of maintaining the mosque's assets. Namira Mosque is one of the mosques that has various programs for its congregation, guaranteed cleanliness, and good facilities, thereby increasing comfort in worship. Therefore, the Namira Mosque is always busy with visitors, of course, this cannot be separated from how the mosque takmir manages the assets of the Namira Mosque so that the benefits can be felt by the congregation directly. The impact of implementing the Nazir strategy in operational management can be felt directly by the congregation through the various facilities and programs available at the Namira Mosque. The suggestion for future researchers is to research more deeply regarding the operational management of waqf assets, especially waqf assets in the form of mosques. Because many mosques still have waqf status but do not have a modern mosque management system for managing their waqf assets, the function of the mosque cannot be carried out optimally.